Stephen King's "Needful Things": a dystopian vision of capitalism during its triumph. Issue 3 (3rd July 2021) - Cedrini, Mario; Dagnes, Joselle; Akdere, Çinla
Abstract: In Stephen King's horror novel Needful Things, a stranger comes to town and opens a shop wherein any inhabitant can find exactly the thing s/he desires most, in exchange for playing "pranks" that cause distress to other members of the community, until the whole town is caught in a war of all against all. The paper analyses the novel as a "satire of Reaganomics, " as the author himself happened to describe it. Using insights from economics, economic sociology, and economic anthropology, it aims at demonstrating that the book provides an opportunity to explore the actual and possible evolution of individual behavior in consumer societies, as well as the tensions that such societies engender between ideals of self-realization ( via market logics and consumption) and social relationships.